Shell model analysIs of pairing excitations in the region 52 ≦ A ≦ 60 - Bés, Daniel; Maqueda, E.; Perazzo, R. P. J. (North Holland Publishing, 1973)
Fil: Bés, Daniel Comisión Nacional de Energía Atómica; Argentina